Medidas de protección social para minimizar el impacto derivado de las fumigaciones en bananeras de la parroquia Barbones- 2023 - Mejía Salas, Anthony Alexis; Naspud Neira, Gustavo Javier (Machala, 2024)
The high use of agricultural chemicals in the province of El Oro affects biodiversity due to the toxicity of these products and the disinfection programs implemented to meet banana production standards. However, the Barbones parish faces the challenge of soil contamination from chemicals used to control diseases in the banana plantations, some of which can be carcinogenic, while aerial spraying has increased allergies and skin diseases. The main objective of this study is to identify the social protection measures implemented to minimize the impact of spraying in banana plantations in the Barbones parish in the year 2023. To achieve this objective, specific objectives were established that include identifying the repercussions faced by workers, determining the social protection measures used, identifying the consequences of not implementing social protection measures, and examining the actions taken by the authorities and producers in the parish. The findings allow the identification of the repercussions faced by banana plantation workers when directly exposed to fumigation, in which the high incidence of health impacts highlights the need to review and improve occupational safety practices, prioritizing the health of workers. Likewise, environmental concerns about soil contamination and impacts on flora and fauna demonstrate the importance of adopting more sustainable agricultural methods, supporting the importance of a comprehensive strategy to protect the health of workers and the environmental balance of Barbones Parish. As regards the social protection measures available to workers, a large percentage of them have the necessary labor protection measures, among which labor insurance is an important guarantee. In the area of social assistance, priority is given to medical assistance; in the area of social security, the taking out of health insurance by employers has become an active measure. However, the need to review and strengthen existing policies to ensure equitable access to all social protection measures for all workers in the banana industry was highlighted. The lack of social protection measures in banana plantations highlights the urgency of implementing them in a comprehensive manner, not only to address immediate risks but also to prevent chronic diseases resulting from prolonged exposure to this work environment. Failure to implement these measures will not only harm the health and safety of workers, but will also have a negative impact on the productivity and long-term sustainability of the banana industry. When examining the actions taken by parish authorities and producers in response to the effects of spraying in banana plantations, a diversity of interventions was observed. Training becomes an important measure for the authorities, highlighting the importance of education in risk mitigation. For producers, the provision of protective tools is the main action, however, the lack of action points to the need for authorities and producers to intensify measures to ensure safe and healthy working conditions in banana plantations. The proposal arises as a response to the intrinsically risky nature of this industry, as workers face health problems ranging from exposure to chemicals to microbiological hazards, and it is essential to address these risks through a proactive strategy that puts the safety and well-being of workers at the forefront, focusing on the economic viability and long-term sustainability of banana plantations. It is also an opportunity to foster a culture of safety in the workplace, reinforcing the idea of how important biosafety is for everyone, considering this participation essential for the plan to work in the long term and to create a safe and sustainable workplace. Thus, by including workers in the development and implementation of the plan, it also reinforces the idea of how important biosafety is for everyone, considering this participation essential for the plan to work in the long term and to create a safe and sustainable workplace.
la cual la alta incidencia de impactos en la salud, resalta la necesidad de revisar y mejorar las prácticas de seguridad ocupacional, priorizando la salud de los trabajadores. Asimismo, las preocupaciones ambientales por la contaminación del suelo y el impacto sobre la flora y la fauna demuestran la importancia de adoptar métodos agrícolas más sostenibles, apoyando la importancia de una estrategia integral que proteja la salud de los trabajadores y el equilibrio ambiental de la Parroquia de Barbones. En lo que respecta a las medidas de protección social de las que disponen los trabajadores, un gran porcentaje de ellos cuenta con las medidas de protección laboral necesarias, entre las cuales el seguro laboral es una garantía importante. En el ámbito de la asistencia social, se da prioridad a la asistencia médica; en el ámbito de la seguridad social, la contratación de un seguro médico por parte de los empleadores se ha convertido en una medida activa. Sin embargo, se destacó la necesidad de revisar y fortalecer las políticas existentes para garantizar el acceso equitativo a todas las medidas de protección social para todos los trabajadores de la industria bananera. La falta de medidas de protección social en las plantaciones bananeras resalta la urgencia de implementarlas de manera integral, no sólo para abordar los riesgos inmediatos sino también para prevenir enfermedades crónicas derivadas de la exposición prolongada a este entorno laboral. La falta de estas medidas no sólo perjudicará la salud y la seguridad de los trabajadores, sino que también tendrá un impacto negativo en la productividad y la sostenibilidad a largo plazo de la industria bananera. Al examinar las acciones tomadas por autoridades parroquiales y productores ante los efectos de las fumigaciones en las plantaciones bananeras, se observó diversidad de intervenciones. La capacitación se convierte en una medida importante para las autoridades, resaltando la importancia de la educación en la mitigación de riesgos. Para los productores, la provisión de herramientas de protección es la acción principal, sin embargo, la falta de acción apunta a la necesidad de que autoridades y productores intensifiquen medidas para garantizar condiciones de trabajo seguras y saludables en las plantaciones bananeras. La propuesta surge como respuesta a la naturaleza intrínsecamente riesgosa de esta industria, debido a que los trabajadores enfrentan afectaciones a su salud, desde la exposición a productos químicos hasta riesgos microbiológicos, considerando fundamental enfrentar estos riesgos a través de una estrategia proactiva que ponga en primer plano la seguridad y el bienestar de los trabajadores, enfocada en la viabilidad económica y la sostenibilidad a largo plazo de las bananeras. Asimismo, es una oportunidad para fomentar una cultura de seguridad en el lugar de trabajo, reforzando la idea de lo importante que es la bioseguridad para todos, considerando esta participación esencial para que el plan funcione a largo plazo y para crear un lugar de trabajo seguro y sostenible. De tal manera que, al incluir a los trabajadores en la elaboración y puesta en marcha del plan, también se refuerza la idea de lo importante que es la bioseguridad para todos, considerando esta participación esencial para que el plan funcione a largo plazo y para crear un lugar de trabajo seguro y sostenible.
Keywords: PROTECCION SOCIAL; FUMIGACION BANANERA; CONTAMINACION